Study the Role of Ph in Curli Biogenesis Gene Expression in Enterobacter Cloacae Local Isolates - Marrib N. Rasheed1 , Basima Qasim Hasan Al-Saadi1 , Osama Mohammed Hasan2 , Noor Yahy Salman1 , Sara (Indian Journal of Forensic Medicine & Toxicology, 2021)
Enterobacter cloacae is the most common pathogenic species of the genus Enterobacter, identified inhospitalized and enfeebled patients as the etiologic agent of many infections and considered as a significantbacterial pathogen in recent years. E. Cloacae are typical gram negative opportunistic forms of bacteria thatcause illness after another infection or injury has influenced the host immune system and are related withnosocomial infections. The infection may be caused by GIT, UTI or cross contamination of the blood. Thepresent study focused on the existence of the main curli biogenesis gene (csgA) and the role of pH as anenvironmental factor in the gene expression (csgA) for curli biogenesis. In this study, urine samples from75 patients.In Baghdad city clinically diagnosed with urinary tract infection,for gram staining, Api20Systemand gene expression (csgA) gene in Standardized pH7 and acid pH4 RT-PCR was performed with specificprimers. Conventional gram staining techniques, agricultural methods and System API 20E showed goodresults for E. Cloacae. For the 75 patients, 10 (13.3%) the findings find the highest gene expression foldvalues for the (csgA)gene in pH7 while the lowest fold value for (csgA) at acid pH4 (0.1577) thus themodify conditions growth such as pH of bacteria E. Cloacae triggers gene expression changes for biogenesisprocess. the findings of rpoB gene expression, which was used as a control gene, indicated that this gene wasgood as a housekeeping gene.